2010
DOI: 10.1080/01490450903393066
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and Bacterial Diversities of Desert Sand Grains from South-East Morocco

Abstract: International audienceMineralogy and microbiology of sand from Merzouga (Morocco) were simultaneously characterized, with the purpose of contributing to a better understanding of the geomicrobiology of deserts. In spite of very low measured bacterial biomass, bacterial diversity on each of the five defined mineralogical classes, was found high. An original grain by grain cultivation method enabled to obtain bacterial isolates with an unusually high recovery rate. The results of this study show that the genus A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 24 publications
7
31
0
Order By: Relevance
“…In such open soil environments, the heterogeneous distribution of minerals can create spatial variability in microhabitats and in (bio)available chemical elements. This has been observed in a culture‐dependant study on dune sand grains from the Merzouga Desert (Morocco), where bacterial diversity was found related to different mineralogies (Gommeaux et al ., ). Carson et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In such open soil environments, the heterogeneous distribution of minerals can create spatial variability in microhabitats and in (bio)available chemical elements. This has been observed in a culture‐dependant study on dune sand grains from the Merzouga Desert (Morocco), where bacterial diversity was found related to different mineralogies (Gommeaux et al ., ). Carson et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, micro‐organisms contribute to the weathering of rock formations in desert ecosystems (Chen et al ., ; Borin et al ., ; Kutovaya et al ., ) and microbial community structures are influenced by the substrate mineral composition (Gommeaux et al ., ; Pietrasiak et al ., ; Steven et al ., ). An analysis of the influence of soil parental material on the distribution of microbial soil crusts in the Mojave and Colorado Deserts (Pietrasiak et al ., ) demonstrated that the proximity to granite bedrock and its associated ‘grusy’ granite soils were key determinants in crust distribution, indicating the importance of geology in shaping desert microbial soil crusts.…”
Section: Introductionmentioning
confidence: 99%
“…Using the live stain technique of Gommeaux et al [], we confirmed that microbes were present on sand grains sampled below the upwind slope of the same dune (Figure ). There, we also found evidence of biological respiration by collecting gas samples at depths of 30, 60, and 90 cm in April 2012.…”
Section: Microbiological Implicationsmentioning
confidence: 99%
“…[5] Recently, Gommeaux et al [2010] and Heulin et al [2003Heulin et al [ , 2012 showed that BSCs and plant rhizospheres are not alone in harboring desert microbes. They found that stationary, nonvegetated desert sand dunes in southeast Morocco contained approximately a thousand culturable microbes for every gram of sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation